16. ANALISIS FAKTOR-FAKTOR PENGHAMBAT RATIFIKASI PORT STATE MEASURES AGREEMENT OLEH INDONESIA PERIODE 2009-2014 - Alghifari, Fadhil; Utomo, Tri Cahyo; Puspapertiwi, Sheiffi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Indonesia, the world's largest archipelago, is known for its rich marine biodiversity andresources. The vast area, however, is difficult to monitor, which give rise to illegalactivities. IUU fishing costs the country 30 trillion rupiah annually. Indonesia remainscommitted to completely eradicate illegal, unreported and unregulated (IUU) fishingactivities through international forum such as FAO. FAO's Port State Measures Agreement(PSMA) 2009 is a testament of commitment from the international community inaddressing IUU fishing by strengthening the role of state port. However, five years afterthe inception of the Agreement, Indonesia's effort in commiting and complying with theAgreement were hampered by several factors. This study is aimed to explain the obstaclesfaced by Indonesia in the process of PSMAâ€™s ratification. Therefore, it enables the countryto conduct unilateral measure in fighting IUU fishing namely the â€œvessel drowningâ€ policywith its current capabilities, available resources, and national interest. These two premisescontribute to the slow process of PSMAâ€™s ratification. This research utilized descriptiveanalyticalmethod in attempt to answer the research question. Based on wide range data,study cases, and the theoretical framework, this study found that the use of Realismparadigm and Oona Hathawayâ€™s integrated theory of International Law could best explainthe hindrances faced by Indonesia in fulfiling the requirements of PSMA 2009, whichhinders the progress of its ratification. This suggests that Indonesian government wouldserve its very best interest solely for the state and its survival in deterring, preventing, andeliminating IUU fishing. Thus, it sets aside the stateâ€™s desire and importance in complyingand committing to international norms.